The past and the present through phylogenetic analysis: the rove beetle tribe Othiini now and 99 Ma. (12th June 2018) - Kypke, Janina L.; Solodovnikov, Alexey; Brunke, Adam; Yamamoto, Shûhei; Żyła, Dagmara
Abstract: In order to classify and taxonomically describe the first two fossil Othiini (Coleoptera: Staphylinidae: Staphylininae) species from three well‐preserved specimens in Cretaceous Burmese amber, a phylogenetic analysis was conducted, combining extant and extinct taxa. A dataset of 76 morphological characters scored for 33 recent species across the subfamilies Staphylininae and Paederinae was analysed using maximum parsimony and Bayesian inference methods. The many differing phylogenetic hypotheses for higher‐level relationships in the large rove beetle subfamilies Staphylininae and Paederinae were summarized and their hitherto known fossil record was reviewed. Based on the analyses, the new extinct genus Vetatrecus gen.n. is described with two new species: V. adelfiae sp.n. and V. secretum sp.n. Both species share character states that easily distinguish them from all recent Othiini and demonstrate a missing morphological link between subfamilies Staphylininae and Paederinae. This is the first morphology‐based evidence for the paraphyly of Staphylininae with respect to Paederinae, suggested earlier by two independent molecular‐based phylogenies of recent taxa. Our newly discovered stem lineage of Othiini stresses the importance of fossils in phylogenetic analyses conducted with the aim of improving the natural classification of extant species. It also suggests that the definitions of Staphylininae and Paederinae, long‐established family‐group taxa, may have to be reconsidered. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:817F39C4-F36B-4FD9-96CD-5F8FB064C39E . Abstract : The first fossil Othiini found in Burmese amber is described in the extinct genus Vetatrecus gen.n. with two species V. adelfiae sp.n. and V. secretum sp.n. To robustly resolve the systematic position of the extinct genus, we applied morphology‐based phylogenetic analysis. With its unique morphology Vetatrecus combines characters that in recent taxa only occur separately in different subfamilies. This stresses the value of fossils for systematics.